A New Species of Lychnophora Mart. (Vernonieae: Asteraceae) from Minas Gerais State, Brazil - Marques, Danilo (2018)
The genus Lychnophora (Vernonieae: Asteraceae) comprises ca. 23 species restricted to Bahia, Goiás, Minas Gerais, and São Paulo States, Brazil. Diamantina's Plateau in the Espinhaço Range of Minas Gerais State is the Brazilian area considered to have the highest endemism and microendemism of Lychnophora. Lychnophora semirii, a new species of the campo rupestre vegetation is described, illustrated, and the affinities between species are discussed. Lychnophora semirii is easily recognized by glutinous leaves with auriculate bases, isolated heads disposed in a corymbiform branches, and a pappus with a conspicuous coroniform outer series. This species currently appears to be a microendemic, as it was found so far only in the Parque Estadual do Biribiri at Diamantina municipality. It is critically endangered due to restricted distribution and habitat vulnerability.